Food security in developing countries: Gender and spatial interactions - Romero Hernandez, Catalina; Wichmann, Bruno; Luckert, Martin K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This brief summarizes findings of a project entitled “Food Security in Developing Countries: Gender and Spatial Interactions’” undertaken by researchers from the University of Alberta. The project uses a large cross-sectional dataset from the Integrated Modelling Platform for Mixed Animal Crop systems (IMPACT) Lite collected by Climate Change, Agriculture, and Food Security (CCAFS) from 2010 to late 2012. This dataset surveyed 1,500 households located across seven countries in Africa and Asia. The project focused on estimating three spatial effects on food security: i) a spatial autoregressive effect that measures how neighbors’ food security influences a farmer’s food security; ii) how these spatial effects differ for male and female-headed households; and iii) how the food security of neighbors of the same gender affect their own food security.